2022
DOI: 10.3389/fonc.2022.919027
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Cumulative Dose and Polymorphisms in CYP2B6 on the Mitotane Plasma Trough Concentrations in Chinese Patients With Advanced Adrenocortical Carcinoma

Abstract: Mitotane is the only drug approved to treat adrenocortical carcinoma (ACC), and a relationship of pharmacokinetic/pharmacodynamic has been characterized. However, limited evidence concerning affecting factors in large interindividual variability of the pharmacokinetics of mitotane is available. To address this question, a retrospective analysis was performed on ACC Chinese patients treated with mitotane for more than 3 months. Mitotane plasma trough concentrations were detected at the steady state, and CYP2B6,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…The polymorphism of CYP enzymes could be involved in the individual variability of the therapeutic effect of mitotane. It has been demonstrated that CYP2B6 is a key cytochrome for mitotane metabolism and that its genetic profile can predict the circulating concentration of mitotane ( 28 30 ). In fact, patients with the wild-type “G” allele achieved lower mitotane concentrations than the patient carrying the mutant “T” allele ( 28 ).…”
Section: Discussionmentioning
confidence: 99%
“…The polymorphism of CYP enzymes could be involved in the individual variability of the therapeutic effect of mitotane. It has been demonstrated that CYP2B6 is a key cytochrome for mitotane metabolism and that its genetic profile can predict the circulating concentration of mitotane ( 28 30 ). In fact, patients with the wild-type “G” allele achieved lower mitotane concentrations than the patient carrying the mutant “T” allele ( 28 ).…”
Section: Discussionmentioning
confidence: 99%